Pengaruh Maleated Natural Rubber Terhadap Morfologi Dan Sifat Thermoset Rubber Dengan Filler Abu Sawit - Carbon Black - Nanda, Hara Novarisa; Bahruddin, Bahruddin; Fadli, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Oil palm ash is a solid waste that is generated from the burning of oil palm shell. It was assumed, this material can be a filler to improve the properties of thermoset rubber because it contains elements of silica. It is expected processing the filler to nano size, the filler can blend with (TR) thermoset Rubber for the improvement. This study aims to improve the properties and morphology of natural rubber-based thermoset rubber by using oil palm ash as filler. Nanofiller-making process begins with the conversion of oil palm ash size into nanometer sizes using ballmill.  Variable levels of research was nanofiller (30 and 50 phr), the ratio of palm ash / carbon black (0/100, 30/70 and 50/50), concentrations of coupling agent MNR (maleated natural rubber) 1.3 and 5 phr. Rubber compound made by mixing natural rubber and nanofiller into rollmill with MNR coupling agent, additives ZnO, Stearic Acid, TMQ (Trimethylquinone), MBTS (Mercaptodibenzothiazyldisulfide) and sulfur for ± 50 minutes. After the rubber mastication, molding was done using hot press at temperature of 200oC and pressure of 50 kgf / cm 2 for 10 minutes. Once formed, the thermoset rubber was exposed to some testing which were mechanical properties, namely tensile strength, elongation at break, tension set using the ISO 527-2 standard type 5A with UTM (Universal Testing Machine), Hardness Test, abrasion test, water absorption test. And analysis of SEM (Scanning Electron Microscopy) to depict TR morphology. The results showed the best properties and morphology of TR obtained at 30 phr filler content, 30/70 rasio of palm ash / carbon black and 3 phr MNR content which was 23.214 MPa tensile strenght, 832.641% elongation at break, 1, 77% Tension Set, 58± 5 Shore A Hardness and 0.22 mm3/Kg Abrasion Resistance.  Keyword : Filler Hybrid, Maleated Natural Rubber, Thermoset Rubber, vulcanization